Svensk-Dansk Ordbog – tradition og fornyelse - Kristensen, Kjeld (Nordiske Studier i Leksikografi, 2007)
At present, the Society for Danish Language and Literature is preparing a new largescaled Swedish-Danish dictionary comprising about 50,000 entries. This paper explores the functionalities of the dictionary, the lemma selection and the structure of the entries from the perspective of lexicographic tradition and innovation. First and foremost, the dictionary is to be a L2-L1 reading comprehension dictionary for Danish users, either for consultation on specific comprehension or translation problems, or for general information on Swedish language. The lemma selection is made on the basis of occurrences in various monolingual Swedish dictionaries and bilingual Swedish-Danish dictionaries as well as electronically accessible text banks. Finally, three example entries are presented to demonstrate how the dictionary will provide information about Swedish language on a broader basis than traditionally done by internordic bilingual dictionaries.